High-flux dual-phase percolation membrane for oxygen separation. Issue 15 (December 2019) - Wang, Shu; Shi, Lei; Xie, Zhiang; He, Yuan; Yan, Dong; Li, Man-Rong; Caro, Juergen; Luo, Huixia
Graphical abstract: Highlights: Our dual-phase membrane 60CPO-40PCFO is economical and ecological. The low-cost novel dual phase material is promising for scale up as supported thin film or hollow fiber. A high oxygen permeation rate of 1.00 mL cm −2 min −1 was obtained through the 60CPO-40PCFO membrane. Compared to other CO2 -stable membranes, our dual phase 60CPO-40PCFO membrane shows a double or even triple oxygen flux. 60CPO-40PCFO membrane can be exposed under the CO2 atmosphere on sweep side over > 100 hour. Abstract: A series of composites based on (100- x )wt.%Ce0.9 Pr0.1 O2- δ- x wt.%Pr0.6 Ca0.4 FeO3- δ ( x = 25, 40 and 50) doped with the cheap and abundant alkaline earth metal Ca 2+ at the A-site has been successfully designed and fabricated. The crystal structure, oxygen permeability, phase and CO2 stability were evaluated. The composition of 60wt.%Ce0.9 Pr0.1 O2- δ-40wt.%Pr0.6 Ca0.4 FeO3- δ(60CPO-40PCFO) possesses the highest oxygen permeability among three studied composites. At 1000 °C, the oxygen permeation fluxes through the 0.3 mm-thickness 60CPO-40PCFO membranes after porous La0.6 Sr0.4 CoO3- δ each to 1.00 mL cm −2 min −1 and 0.62 mL cm −2 min −1 under air/He and air/CO2 gradients, respectively. In situ XRD results demonstrated that the 60CPO-40PCFO sample displayed a perfect structural stability in air as well as CO2 -containing atmosphere. Thus, low-cost, Co-free and Sr-free 60CPO-40PCFO has high CO2 stability and is economical and environmental friendly since the expensive and volatile element Co was replaced by Fe and Sr was waived since it easily forms carbonates.